A Comparative Study of Different EEG Reference Choices for Event-Related Potentials Extracted by Independent Component Analysis - Dong, Li; Liu, Xiaobo; Zhao, Lingling; Lai, Yongxiu; Gong, Diankun; Liu, Tiejun; Yao, Dezhong (Frontiers in Neuroscience, 2019)
In event-related potential (ERP) of scalp electroencephalography (EEG) studies, the vertex reference (Cz), linked mastoids or ears (LM), and average reference (AVG) are popular reference methods, the reference electrode standardization technique (REST) is increasingly applied. Because scalp EEG recordings are considered spatially degraded signals, independent component analysis (ICA) is a widely used data-driven method for obtaining ERPs by decomposing EEG data. However, the accurate estimation of the differences in ERP components extracted by ICA with different references remains unclear. In this study, we first provided formal descriptions of the above reference methods (Cz, LM, AVG and REST) and ICA decomposition in ERP and then investigated the influences of different reference techniques on simulation and real EEG datasets. The results revealed that 1) the reference method did not change the peak amplitudes and latencies of relative ERPs corresponding to some IC time courses; 2) there were nonnegligible effects of different reference methods on both temporal ERPs and spatial topographies of some ICs; and 3) compared to Cz, LM and AR, considering both the performances of temporal ERPs and spatial topographies, the REST reference had overall superiority. These findings provide a recommended choice of REST for ICA analysis at the trial level and contribute to empirical investigations regarding the use of reference methods in ERP domains with ICA analysis.